An exploration of patient safety culture in NICUs: a convergent parallel mixed-method study - Mohadese Babaie; Manijeh Nourian; Foroozan Atashzadeh-Shoorideh; Houman Manoochehri; Malihe Nasiri (BMC, 2024)
Abstract Background Safety culture, as a component that improves the quality of safety and health care for neonates, serves as foundation for providing professional and high-quality care by creating positive insight among employees. This study aimed to explore the safety culture concept in neonatal intensive care units (NICUs). Methods This convergent parallel mixed-method study included Quantitative, Qualitative, and Integrated parts. In the Quantitative part, the psychometric properties of the Persian version of "Hospital Survey on Patient Safety Culture" were examined among physicians and nurses in NICUs. CFA was performed on the data obtained from 342 participants. The Qualitative section data were collected through in-depth and semi-structured interviews with 24 staff to understand the concept of safety culture. Data were analyzed through the Elo & Kyngäs approach. The interpretation of the results and the convergence of the data was done using the Onwuegbuzie and Teddlie method. Results The initial CFA showed that the 12-dimensional model did not align well with indices. Subsequently, based on T-values, six heterogeneous items were eliminated. The revised 11-dimensional model consisting of 36 items showed an acceptable fit during the second CFA. In the qualitative part, five main categories of "Constructive interactions", "Management's commitment to neonatal safety", "Organizational supportive climate", "Professional development", and "Planning and implementation of neonatal developmental care" were obtained. The comparison of the results showed that the dimensions of the quantitative part, except for "Overall perceptions of patient safety", were also present in the qualitative part, but they were different in some aspects. New findings in the qualitative study such as "Striving for mutual empowerment", "Constructive criticism in teamwork", "Efficient supervision procedures", "Inexperienced staff' leading" and "Provision of care assistance equipment and facilities" were not found in the dimensions of the quantitative part. The main categories "Acquiring professional competence" and "Planning and implementation of neonatal developmental care" were not align with the dimensions identified in the quantitative study. Conclusion The findings shed light on previously unexplored aspects of the safety culture concept within the nursing profession, leading to a better understanding and evolution of this concept in Iranian NICUs. The new definition obtained in this study can enhance nursing knowledge on safe care and improve patient safety culture in the NICUs in Iran and globally.